Lawsonia Inermis Linn: A Plant with Cosmetic and Medical Benefits - Sharma, Ritesh Kumar; Goel, Anjana; Bhatia, A. K. (International Journal of Applied Sciences and Biotechnology, 2016)
Plants play a major role on the earth and human beings depend on plants because of their medicinal properties. About 80% of the world population using plants as a medicinal drugs because plants have no side effects and show synergistic effect unlike modern medicine. In the present study, review and authentication of the various aspects of the plant Lawsonia inermis was carried out. This plant is mainly present in subtropical and tropical areas and is used in all over the world. The common name of L. inermis is Henna and Mehndi. It has been used for over 9000 years for their cosmetic values as a dye. Traditionally, in Asian countries like India and Pakistan, plant leaves are applied to hands, hairs and feet. Morphologically the plant is a small tree or shrub. L. inermis is cultivated for roots, flowers, stem bark and seeds for their medicinal uses. Proteins, carbohydrates and fatty acid are primary metabolites along with secondary metabolite such as tannins, quinines, terpenoids, coumarins etc which are present in L. inermis plant. Phytochemical constituents of L. inermis are responsible for its analgesic, anti-inflammatory, hepatoprotective and hypoglycaemic properties. The plant has also been reported for antibacterial, antifungal, immunostimulatory, antioxidant and cytotoxic activity. Presence of these properties in L. inermis plant develops it as medicine against various pathogenic organism and diseases. This review gives a wide view on the phytochemistry, pharmacological properties and traditional uses of the plant. Int J Appl Sci Biotechnol, Vol 4(1): 15-20